Impact of prior SARS-CoV-2 infection on incidence of hospitalization and adverse events following mRNA SARS-CoV-2 vaccination: A nationwide, retrospective cohort study. Issue 8 (16th February 2022) - Li, Lucy L.; Zheng, Chunlei; La, Jennifer; Do, Nhan V.; Monach, Paul A.; Strymish, Judith M.; Fillmore, Nathanael R.; Branch-Elliman, Westyn
Abstract: Background: Previous studies evaluated the SARS-CoV-2 vaccine safety or compared adverse events following vaccination to those from infection. Limited data about the impact of prior infection on post-vaccine adverse events are available. The objective of this study was to evaluate the impact of prior SARS-CoV-2 infection on outcomes shortly after vaccination using a longitudinal design. Methods: Nationwide, multicenter, retrospective cohort study of hospitalization, death, and pre-specified adverse event rates among Veterans who received mRNA vaccines within the Veterans Health Administration between 12/11/2020 and 8/31/2021. Daily incidence rates were compared before and after vaccine doses, stratified by history of microbiologically-confirmed SARS-CoV-2. Results: 3, 118, 802 patients received a first dose and 2, 979, 326 a second, including 102, 829 with a history of SARS-CoV-2 infection. Daily incident hospitalization rates were unchanged before and after the second dose among patients without previous infection (28.8/100, 000 post-dose versus 28.6/100, 000 pre-dose, p = 0.92). In previously-infected patients, the hospitalization rate increased above baseline one day following vaccination (158.2/100, 000 after dose 2 versus 57.3/100, 000 pre-dose, p < 0.001), then returned to baseline. Chart review indicated vaccine side effects, such as fever, constitutional symptoms, weakness, or falls, as the definite (39%) or possible (18%) cause of hospitalization. Affected patients had mean age 75, and 90% had at least one serious comorbidity. Hospitalizations were brief (median 2 days), with rapid return to baseline health. Worse baseline health among previously-infected patients prevented conclusions about mortality risk. Conclusions: Two-dose mRNA vaccine regimens are safe in a population with many comorbidities. Transient increased risks of hospitalization were identified among patients with prior SARS-CoV-2, absolute risk ∼1:1000. Findings support additional study regarding the optimal dosing schedule in this population. Funding: None.